AP-1/IRF-3 Targeted Anti-Inflammatory Activity of Andrographolide Isolated from Andrographis paniculata. (6th June 2013) - Shen, Ting; Yang, Woo Seok; Yi, Young-Su; Sung, Gi-Ho; Rhee, Man Hee; Poo, Haryoung; Kim, Mi-Yeon; Kim, Kyung-Woon; Kim, Jong Heon; Cho, Jae Youl
Abstract : Andrographolide (AG) is an abundant component of plants of the genus Andrographis and has a number of beneficial properties including neuroprotective, anticancer, anti-inflammatory, and antidiabetic effects. Despite numerous pharmacological studies, the precise mechanism of AG is still ambiguous. Thus, in the present study, we investigated the molecular mechanisms of AG and its target proteins as they pertain to anti-inflammatory responses. AG suppressed the production of nitric oxide (NO) and prostaglandin E2 (PGE2 ), as well as the mRNA abundance of inducible NO synthase (iNOS), tumor necrosis factor-alpha (TNF- α ), cyclooxygenase (COX)-2, and interferon-beta (IFN- β ) in a dose-dependent manner in both lipopolysaccharide- (LPS-) activated RAW264.7 cells and peritoneal macrophages. AG also substantially ameliorated the symptoms of LPS-induced hepatitis and EtOH/HCl-induced gastritis in mice. Based on the results of luciferase reporter gene assays, kinase assays, and measurement of nuclear levels of transcription factors, the anti-inflammatory effects of AG were found to be clearly mediated by inhibition of both (1) extracellular signal-regulated kinase (ERK)/activator protein (AP)-1 and (2) I κ B kinase ε (IKK ε )/interferon regulatory factor (IRF)-3 pathways. In conclusion, we detected a novel molecular signaling pathway by which AG can suppress inflammatory responses. Thus, AG is a promising anti-inflammatory drug with two pharmacological targets.